TUSC7 acts as a tumor suppressor in colorectal cancer - Ren, Weidan (Am J Transl Res, 2017)
Increasing studies showed that long non-coding RNAs (lncRNAs) played important roles in the development and progression of tumors. Previous evidences suggested that Tumor suppressor candidate 7 (TUSC7) was involved in several tumors initiation. However, the role of TUSC7 in colorectal cancer is still unknown. In this study, we indicated that the expression of TUSC7 was downregulated in colorectal cancer cell lines and tissues. Moreover, the expression of TUSC7 was lower in the high-grade (Dukes C and D) colorectal cancer patients compared to that in the low-grade colorectal cancer patients (Dukes A and B). Colorectal cancer patients with a lower level of TUSC7 expression had worse overall survival rate. Elevated expression of TUSC7 suppressed SW480 and HT29 cell proliferation and invasion. In addition, we demonstrated that overexpression of TUSC7 inhibited the expression of miR-10a and enhanced the expression of PTEN and EphA8, which were the direct target genes of miR-10a. Furthermore, the expression of miR-10a was upregulated in colorectal cancer cell lines and tissues. TUSC7 suppressed colorectal cancer cell proliferation and invasion partly through targeting miR-10a. These results suggested that TUSC7 played as a tumor suppressor gene in colorectal cancer partly through inhibiting miR-10a expression.